Exploring Greek History: “Odisseia a Sabedoria - A Jornada de Atenas” in an Educational Digital Game - Matos, Mikaelly Elídia; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33691, 2024)
This article introduces “Odisseia à Sabedoria - A Jornada de Atenas,” a digital game designed to teach Ancient Greek history to middle school students. Created using the Unity 3D platform and aligned with curricular goals, the game provides an immersive experience in historical events and Greek mythology. The development followed an iterative-incremental agile methodology, allowing for continuous adjustments based on feedback from tests conducted in public schools. The interactive environment of the game plays a key role in the students' learning process. Initial results highlight the effectiveness of digital games in history education and the importance of technology in modern education.